Structural Use of Lexical Bundles in the Rhetorical Moves of L1 and L2 Academic Writing - Hong, Ji-yoon (English Teaching, 2019)
This corpus-driven longitudinal study investigates the structural use of lexical bundles in published research article (RA) introductions in applied linguistics written by English experts and Korean graduate students across two different levels of study. Frequency-based bundles were retrieved from a corpus of 200 published RA introductions and two corpora of 46 and 49 introductions of term papers written at two time points of the first and fourth semester of graduate course. In a further step, the structures of the bundles in different rhetorical moves of RA introductions were analyzed to reveal the developmental patterns in bundle use. The analyses show that the Korean graduate students are in the developmental process of academic writing featured by a shift from clausal style to phrasal style as their academic level advances. The results also suggest that the students have difficulty in appropriate bundle use in specific rhetorical moves even at the later academic level of graduate coursework. The pedagogical implications of L2 students' developmental order are discussed.